Atlas Technology, a Digital Framework for Efficient Management and Use of Regional Data. The Argentina Satellite Atlas - Asato, Carlos Gabriel (2005)
Trabajo presentado en: International Association for Mathematical Geology. Toronto, Canada. Agosto 21 a 26 de 2005.